2008
DOI: 10.1111/j.1365-2656.2008.01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical defences wear you down: progressive and irreversible impacts of silica on insect herbivores

Abstract: Summary 1.Silica in the leaves of grasses can act as a defence against both vertebrate and invertebrate herbivores. The mechanisms by which silica affects herbivore performance are not well characterized. Here we expose an insect herbivore Spodoptera exempta to high-silica diets and test two mechanisms by which silica has been proposed to act as a defence. First, that silica reduces the digestibility of leaves and second, that silica causes wear to insect mandibles, both of which could potentially impact on he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
317
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(335 citation statements)
references
References 48 publications
(96 reference statements)
13
317
0
5
Order By: Relevance
“…Moreover, silica plays an important role in the interaction between herbivores and plants. Massey et al (2006aMassey et al ( , 2006bMassey et al ( , 2007Massey et al ( , 2008Massey et al ( , 2009 showed that silica accumulation in grasses increases leaf abrasiveness, causing the wear and deterioration of mandibles and impairing insect feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, silica plays an important role in the interaction between herbivores and plants. Massey et al (2006aMassey et al ( , 2006bMassey et al ( , 2007Massey et al ( , 2008Massey et al ( , 2009 showed that silica accumulation in grasses increases leaf abrasiveness, causing the wear and deterioration of mandibles and impairing insect feeding.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the resistance conferred by the leaf silicon application causes chemical and physical changes in three varieties of Poaceae (Deschampsia caespitosa L, Festuca ovina and Lolium perene L.) such as reduced digestibility, increased tissue stiffness and increased abrasiveness [30]. However, with application of calcium silicate in the soil, it was already observed in coffee that the mealybug, P. citri, reached the phloem feeding place without problems, indicating that in this study, no mechanical barrier was performed to avoid the penetration of the buccal stylets [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although the role deposited silicon plays in enhancing defences against plant pathogens is well established, there is also evidence that silicon content is directly correlated with resistance to herbivory (Massey and Hartley, 2009;Hunt et al, 2008). This resistance to herbivory is thought to be due to a reduction in palatability for the herbivore.…”
Section: Chapter 7 -Discussion and Conclusionmentioning
confidence: 99%
“…This resistance to herbivory is thought to be due to a reduction in palatability for the herbivore. Massey and Hartley (2009) found that organisms feeding on silicon-rich material plant material did not adapt with age and theorised that organisms have a limited capacity for developing a tolerance to silicon-rich plant tissue. This suggests that silicon deposition provides plants with an evolutionary advantage against herbivores, and it would be interesting to compare silicon deposition with the presence of anti-herbivore toxins to see if there is a negative correlation.…”
Section: Chapter 7 -Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation